Probiotic Lactobacilli Modulate Staphylococcus aureus-Induced Activation of Conventional and Unconventional T cells and NK Cells - Johansson, Maria A.; Björkander, Sophia; Mata Forsberg, Manuel; Qazi, Khaleda Rahman; Salvany Celades, Maria; Bittmann, Julia; Eberl, Matthias; Sverremark-Ekström, Eva (Frontiers in Immunology, 2016)
Lactobacilli are probiotic commensal bacteria and potent modulators of immunity. When present in the gut or supplemented as probiotics, they beneficially modulate ex vivo immune responsiveness. Further, factors derived from several lactobacilli strains act immune regulato-ry in vitro. In contrast, Staphylococcus aureus (S. aureus) is known to induce excessive T cell activation. In this study we aimed to investigate S. aureus-induced activation of human muco-sal associated invariant T cells (MAIT cells), γδ T cells, NK cells, as well as of conventional CD4+ and CD8+ T cells in vitro. Further, we investigated if lactobacilli-derived factors could modulate their activation. PBMC were cultured with S. aureus 161:2 cell free supernatant (CFS), staphylococcal en-terotoxin A or CD3/CD28-beads alone or in combination with Lactobacillus rhamnosus (L. rhamnosus) GG-CFS or Lactobacillus reuteri (L. reuteri) DSM 17938-CFS, and activation of T and NK cells was evaluated. S. aureus-CFS induced IFN-γ and CD107a expression as well as proliferation. Co-stimulation with lactobacilli-CFS dampened lymphocyte activation in all cell types analysed. Pre-incubation with lactobacilli-CFS was enough to reduce subsequent activation and the ab-sence of APC or APC-derived IL-10 did not prevent lactobacilli-mediated dampening. Final-ly, lactate selectively dampened activation of unconventional T cells and NK cells. In summary, we show that molecules present in the lactobacilli-CFS are able to directly dampen in vitro activation of conventional and unconventional T cells and of NK cells. This study provides novel insights on the immune modulatory nature of probiotic lactobacilli and suggests a role for lactobacilli in modulation of induced T and NK cell activation.